Protein Kinase C-ε Promotes EMT in Breast Cancer. (January 2014) - Jain, Kirti; Basu, Alakananda
Protein kinase C (PKC), a family of serine/threonine kinases, plays critical roles in signal transduction and cell regulation. PKCε, a member of the novel PKC family, is known to be a transforming oncogene and a tumor biomarker for aggressive breast cancers. In this study, we examined the involvement of PKCε in epithelial to mesenchymal transition (EMT), the process that leads the way to metastasis. Overexpression of PKCε was sufficient to induce a mesenchymal phenotype in non-tumorigenic mammary epithelial MCF-10 A cells. This was accompanied by a decrease in the epithelial markers, such as E-cadherin, zonula occludens (ZO)-1, and claudin-1, and an increase in mesenchymal marker vimentin. Transforming growth factor β (TGFβ) induced Snail expression and mesenchymal morphology in MCF-10 A cells, and these effects were partially reversed by the PKCε knockdown. PKCε also mediated cell migration and anoikis resistance, which are hallmarks of EMT. Thus, our study demonstrates that PKCε is an important mediator of EMT in breast cancer.